Effects of spray dried plasma on litter growth performance and oxidative stress and inflammation of sows kept in a hot environment - Hannah M. Bailey; Natalia S. Fanelli; Joy M. Campbell; Hans H. Stein (Journal of Animal Science and Biotechnology)
Abstract Background Feeding spray dried plasma (SDP) to weanling pigs improves growth, but there is a lack of research on how SDP impacts oxidative stress and inflammatory response in lactating sows, and performance of their piglets after weaning. Therefore, an experiment was conducted to test the hypothesis that sows fed a diet with SDP in late gestation and lactation have improved reproductive performance and reduced inflammation compared with sows fed no SDP. The second hypothesis was that pigs weaned from sows fed 0.5% SDP in lactation have reduced diarrhea incidence and improved growth performance during the initial 14 d of the nursery period regardless of dietary SDP. Results The percent of low vitality or starved pigs during lactation was less (P < 0.05) from sows fed 0.5% dietary SDP compared with sows fed the diet without SDP. Dietary SDP did not influence oxidative stress markers in the plasma of sows, but serum cytokines increased (P < 0.05) in sows fed the diet with 0.5% SDP compared with sows fed the diet without SDP. Pigs weaned from young sows fed no SDP or from mature sows fed 0 or 0.5% SDP had a greater gain to feed ratio when fed a phase 1 diet containing 6% SDP compared with pigs fed a diet without SDP, but the gain to feed ratio of pigs weaned from young sows fed 0.5% dietary SDP was not affected by dietary SDP in phase 1 (interaction, P < 0.05). Regardless of sow treatment, pigs fed a phase 1 diet with 6% SDP had greater (P < 0.05) growth performance than pigs fed a phase 1 diet without SDP, and pigs fed the phase 1 diet with 6% SDP had reduced (P < 0.05) diarrhea incidence in phase 1. Conclusions Feeding 0.5% dietary SDP to sows may reduce the number of mummified pigs and increase pig vitality during lactation, but adding 0.5% SDP to sow diets during lactation did not improve post-weaning performance of pigs fed a starter diet with 6% SDP.